A clinicopathologic study of intussusception in Nepalese adults - Shakya, Vikal Chandra; Byanjankar, Bikram; Pandit, Rabin; Shrestha, Anir Ram Moh; Karki, Saurav; Pangeni, Anang (Journal of Society of Surgeons of Nepal, 2020)
Introduction: Intussusception is rate in adults and is usually secondary to a definable pathology. This study was designed to review adult intussusception, including presentation, diagnosis, and pathology. Methods: A retrospective study of 18 cases of intussusception in individuals older than 18 years of age visiting the department of surgery of Civil Service Hospital from 2010 to 2018 was done. Results: There were 18 cases of adult intussusception. The mean age was 49.2 years (range 19-84 years). Abdominal pain and vomiting were the commonest symptoms. The median duration of presentation was 5 days (range 20 hours to 10 months). Three patients (16.6%) presented with generalized peritonitis. There were eight ileocolic, seven ileoileal, and three colocolic intussusceptions. Two patients (11.1%) settled spontaneously. Twelve out of the 18 patients (66.6%) had leading lesions. Benign pathologies were seen in seven cases (38.8%) and malignant in five patients (27.7%). All malignancies were in the large bowl Conclusions: Adult intussusception is a rare entity, nearly one-third of their causes are malignant. Surgery is the best recommended treatment, with or without a primary reduction of the intussusception; the latter can result in more limited bowel resection.